Effects of Conditioning Temperature on Pellet Quality, Nutrients Digestibility, and Metabolizable Energy of Broilers Diet - Seyedeh Vajiheh Shakhese Emampour; Abolghasem Golian; Heydar Zarghi; Ali Reza Hesabi Nameghi (پژوهشهای علوم دامی ایران)
Introduction: Pelleting is one of the most common methods of thermal processing for poultry feed. The primary goal of pelleting is to agglomerate smaller feed particles using mechanical pressure, moisture, and heat. Previous studies have shown that pelleted feeds enhance production economics by improving feed efficiency and growth performance. A key step in the pelleting process is conditioning the mash prior to pelleting, which reduces the electrical energy usage (EEU) of pellet mill motors by facilitating the smooth passage of materials through the die press, playing a crucial role in forming high-quality pellets. Additionally, effect on productive performance, reported conditioning temperature is the main factor affect it. Moderate thermal processing of broiler diets causes the separation of protein matrix, starch and fat, gelatinization of starch, destruction of anti-nutritional sensitive to heat and destruction of cell walls, and are considered positive chemical and physical changes in the process of pelleting with steam heat. Thermal processing improves the nutrient value of broiler diets, which usually has beneficial effects on performance. The use of high conditioning temperatures can damage the nutrients in the feed, leading to reduced nutrient intake and decreased bird performance. However, the better physical quality of pellets obtained at higher conditioning temperatures may affect broiler performance depending on the extent of negative effects of conditioner temperature on nutrient availability. Feed form affects the metabolizable energy of broiler pelleting and increases the apparent metabolizable energy of grains. The objective of the current study was to evaluate the influence of conditioning temperature on EEU of the pellet mill motors, feed pellet quality, apparent metabolizable energy corrected for nitrogen (AMEn), and apparent nutrients digestibility in the broiler chickens.Materials and Methods: A diet were formulated on the broiler Ross 308 strain recommendations bases for grower period. The diet was prepared according to the experimental design, using a completely randomized design (CRD) with 11 treatments and 5 replicates per treatment. The treatments included mash feed, cold pelleting (unconditioned), and pelleting following conditioning at three different temperatures (55, 70, and 85°C), with feed samples collected at three different stages during feed preparation. The diet conditioning was done by conditioner manufactured by Feedtech at steam mixture for 30s and two bar steam pressure and then were pelleted through 2.5 mm die using a pellet mill. The desired temperatures of the conditioner were applied by increasing the volume of steam and continuously measured during the passage of the feed using a digital thermometer. The electrical energy usage (EEU) of the pellet mill motors during the pellet diets predation were recorded. All pellet diets were sampled after production to test for pellet quality. Pellet quality was determined as a function of pellet durability index (PDI), fine percentage and pellet hardness. Durability was determined using a Holmen Pellet Tester (NHP200). The pellet hardness was determined by using a hardness tester. A total of 200 one-day-old male chicks (Ross 308) were purchased from a commercial hatchery, reared on floor covered with wood shavings and the Ross 308 guideline up to 11-day-old. To determine the apparent nutrients digestibility and apparent metabolizable energy corrected for nitrogen (AMEn), two birds were transferred to individual cages (replicate) on day 15 to adapt to cage conditions for 4 days. On d19, birds were subjected to eight hours’ starvation following which collection trays were installed under each cage for excreta collection. Feed intake of the birds in each cage was recorded during the experimental period (19-21d). Total excreta were collected twice daily between 18-21d. Daily collections were immediately dried, pooled within a replicate, mixed, weighed and representative samples ground (0.5 mm sieve), and stored in airtight plastic containers (−20°C) until to analysis. Excreta and diet samples were analyzed for dry matter (DM; method 934.01), crude protein (CP; method 976.06), ether extract (EE; 954.02) according to the standard procedures of the Association of Official Analytical Chemists (AOAC, 2016). Apparent total tract retention coefficient of nutrients for diets were calculated. In addition, the gross energy of feeds and excreta samples were measured using adiabatic bomb calorimeter (Model 1266, PARR) and the apparent metabolizable energy was calculated. The data obtained from the experiment were analyzed in the form of a completely randomized design using SAS software version 9.1 (2003) with the general linear model (GLM) procedure. The respective means were compared with Tukey's test at the probability level (P < 0.05).Results and Discussion: The effects of processing temperature on EEU of the pellet mill motors, and pellet quality were significant. So that the amount of electricity usage decreased (quadratic, p< 0.001), and increased pellet PDI (quadratic, p<0.001) and pellet hardness (linear, p<0.002) by increasing in conditioning temperature. The highest electricity usage was observed in the treatment without conditioning (cold pellet) and the lowest amount of electricity usage was observed in the 70, and 85C° treatments (P<0.05). The diet dry matter, crude protein and crude fat digestibility and AMEn were affected by processing (P>0.05) so that the highest digestibility rate and AMEn was observed in 70°C heat thermal treatment, which were significantly higher than mash diet. By increasing conditioning temperature, the AMEn and crude fat digestibility improved by quadratic trend (p < 0.05). The heat processing at 70°C and pelleting diet lead to 6.8% and 3.59% improving apparent fat digestibility and 96 kcal/kg (3.46%) and 74 kcal/kg (2.64%) improving in AMEn values than non-processed diet (mash diet) and cold pellet diet, respectively.Conclusion:  Based on the findings of this study, it is recommended to prepare feed in pellet form and apply a conditioning temperature of 70°C. This approach reduces the electrical energy consumption during feed preparation, improves pellet quality, and enhances nutrient digestibility and the apparent metabolizable energy (AMEn) of the diet.